Chemocatalytic Conversion of Ethanol into Butadiene and Other Bulk Chemicals - Angelici, Carlo; Weckhuysen, Bert M.; Bruijnincx, Pieter C. A. (ChemSusChem, 2013)
The development of new and improved processes for the synthesis of bio‐based chemicals is one of the scientific challenges of our time. These new discoveries are not only important from an environmental point of view, but also represent an important economic opportunity, provided that the developed processes are selective and efficient. Bioethanol is currently produced from renewable resources in large amounts and, in addition to its use as biofuel, holds considerable promise as a building block for the chemical industry. Indeed, further improvements in production, both in terms of efficiency and feedstock selection, will guarantee availability at competitive prices. The conversion of bioethanol into commodity chemicals, in particular direct ‘drop‐in’ replacements is, therefore, becoming increasingly attractive, provided that the appropriate (catalytic) technology is in place. The production of green and renewable 1,3‐butadiene is a clear example of this approach. The Lebedev process for the one‐step catalytic conversion of ethanol to butadiene has been known since the 1930s and has been applied on an industrial scale to produce synthetic rubber. Later, the availability of low‐cost oil made it more convenient to obtain butadiene from petrochemical sources. The desire to produce bulk chemicals in a sustainable way and the availability of low‐cost bioethanol in large volumes has, however, resulted in a renaissance of this old butadiene production process. This paper reviews the catalytic aspects associated with the synthesis of butadiene via the Lebedev process, as well as the production of other, mechanistically related bulk chemicals that can be obtained from (bio)ethanol. Fuel for thought: The dedicated production of 1,3‐butadiene from bioethanol is expected to be an effective solution to its current substantial price increase. The Lebedev process for ethanol‐to‐butadiene conversion is reviewed in detail. The Review also extends to other commodity chemicals that are produced from ethanol and are involved as intermediates or byproducts in the bio‐based butadiene production process.